Comprehensive analysis of the in vitro and ex ovo hemocompatibility of surface engineered iron oxide nanoparticles for biomedical applications - Schlenk, Florian; Werner, Sebastian; Rabel, Martin; Jacobs, Franziska; Bergemann, Christian; Clement, Joachim H.; Fischer, Dagmar (Archives of Toxicology, 2017)
A set of biomedically relevant iron oxide nanoparticles with systematically modified polymer surfaces was investigated regarding their interaction with the first contact partners after systemic administration such as blood cells, blood proteins, and the endothelial blood vessels, to establish structure–activity relationships. All nanoparticles were intensively characterized regarding their physicochemical parameters. Cyto- and hemocompatibility tests showed that (1) the properties of the core material itself were not relevant in short-term incubation studies, and (2) toxicities increased with higher polymer mass, neutral = anionic < cationic surface charge and charge density, as well as agglomeration. Based on this, it was possible to classify the nanoparticles in three groups, to establish structure–activity relationships and to predict nanosafety. While the results between cyto- and hemotoxicity tests correlated well for the polymers, data were not fully transferable for the nanoparticles, especially in case of cationic low molar mass polymer coatings. To evaluate the prediction efficacy of the static in vitro models, the results were compared to those obtained in an ex ovo shell-less hen’s egg test after microinjection under dynamic flow conditions. While the polymers demonstrated hemotoxicity profiles comparable to the in vitro tests, the size-dependent risks of nanoparticles could be more efficiently simulated in the more complex ex ovo environment, making the shell-less egg model an efficient alternative to animal studies according to the 3R concept.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Blood compatibility; Hen’s egg; Magnetic nanoparticles; Nanosafety; Protein corona